2006
DOI: 10.1038/ncpgasthep0577
|View full text |Cite
|
Sign up to set email alerts
|

Nonmalignant portal vein thrombosis in adults

Abstract: Portal vein thrombosis (PVT) consists of two different entities: acute PVT and chronic PVT. Acute PVT usually presents as abdominal pain. When the thrombus extends to the mesenteric venous arches, intestinal infarction can occur. Chronic PVT is usually recognized after a fortuitous diagnosis of hypersplenism or portal hypertension, or when there are biliary symptoms related to portal cholangiopathy. Local risk factors for PVT, such as an abdominal inflammatory focus, can be identified in 30% of patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
134
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(139 citation statements)
references
References 56 publications
1
134
1
3
Order By: Relevance
“…If the following conditions occur, the possibility of PV-SMV thrombosis should be considered in order to achieve early diagnosis and treatment. largement without apparent splenic hyperfunction; (6) unexplained paralytic intestinal obstruction, necrosis or peritonitis, etc [8,9] . The diagnosis of PV-SMV thrombosis relies on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…If the following conditions occur, the possibility of PV-SMV thrombosis should be considered in order to achieve early diagnosis and treatment. largement without apparent splenic hyperfunction; (6) unexplained paralytic intestinal obstruction, necrosis or peritonitis, etc [8,9] . The diagnosis of PV-SMV thrombosis relies on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Occult MPD as a cause of PVT is seen in 16.7% and classical MPD in 13.8%. 18 The diagnosis of myeloproliferative disorders as a cause of PVT has increased by 20% with the identification of Janus kinase 2 (JAK 2) V617F gene mutation. The presence of JAK 2 mutation is seen in around 17-35% patients of PVT.…”
Section: Acute Non-cirrhotic Portal Vein Thrombosis Procoagulant Statementioning
confidence: 99%
“…Prothrombin levels and other coagulation factors may be decreased while Ddimer is usually increased. 18,84 Patients with portal hypertensive biliopathy may show a rise in alkaline phosphatase. Liver grossly is normal in PVT, but may show atrophy and regenerative nodular hyperplasia, related to apoptosis and compensatory arterial vasodilation in chronic PVT.…”
Section: Liver Functionmentioning
confidence: 99%
“…23 One study showed the figure to be 30.7%, with 16.7% being occult MPD and 13.8% being classical MPD. 24 Another recent study, looking at 44 patients, reported PVT to be the first manifestation of MPD in 31 patients (70%). 25 However, this mutation is not very common in those with PVT secondary to liver disease.…”
Section: Jak2 Mutation and Pvtmentioning
confidence: 99%
“…As is generally the case in venous thrombosis, D-dimer is usually increased and not helpful. 24 It is important to exclude an underlying systemic disorder in those with no local cause identified. All patients without a clearly identifiable cause on imaging should have a JAK2 mutation analysis, lactate dehydrogenase and tests for paroxysmal nocturnal haemoglobinuria , factor V Leiden and prothrombin gene mutations.…”
Section: Blood Testsmentioning
confidence: 99%